2002
DOI: 10.1097/00001888-200211000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Communication Skills

Abstract: As expected, initially some health coach students complained about their perceived increased workloads compared with the workloads of students in the shadowing track. Some students also expressed reservations about their abilities to be effective with their patients, but these complaints diminished as students made contact with patients. For many, this opportunity to establish continuity relationships with patients helped students begin to understand difficulties inherent in effecting health-behavior change. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…One study showed that RES used a large number of jargon words such as gene, sweat test, carrier, and sickle cell during a mock encounter with parents [19]. Additional training such as mock encounters with input from experienced faculty may be useful in boosting RES confidence [20,21]. RES can benefit from improved communication skills not just during encounters for abnormal NBS, but for any situation as it is a necessary part of the core competencies acquired during residency.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that RES used a large number of jargon words such as gene, sweat test, carrier, and sickle cell during a mock encounter with parents [19]. Additional training such as mock encounters with input from experienced faculty may be useful in boosting RES confidence [20,21]. RES can benefit from improved communication skills not just during encounters for abnormal NBS, but for any situation as it is a necessary part of the core competencies acquired during residency.…”
Section: Discussionmentioning
confidence: 99%
“…This again is related to Bandura’s (1997) notion that having a belief that one can use skills facilitates their use. Having staff who communicate better may therefore not only benefit the parent, but also the staff members themselves by providing them with positive reinforcement and enhanced self‐efficacy (Wagner et al. 2002).…”
Section: What This Study Addsmentioning
confidence: 99%
“…The notion of ‘client‐centred’ care places the client in control of their own health, working together with a healthcare practitioner. Client‐centred care has been associated with a range of positive outcomes, such as increased self‐efficacy, compliance with treatment and better clinical outcomes (Wagner et al. 2002, Zachariae et al.…”
Section: Introductionmentioning
confidence: 99%
“…, 2008), improved patient recall and understanding (Zick et al. , 2007) and improved clinical outcomes (Wagner et al. , 2002; Stewart et al.…”
Section: Introductionmentioning
confidence: 99%